2016
DOI: 10.1021/acs.organomet.6b00626
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Manganese and Rhenium Vinylidene Complexes with Hydrophosphoryl Compounds

Abstract: We studied the reactions of manganese and rhenium phenylvinylidenes Cp(CO) 2 MCC(H)Ph (Mn1 M = Mn; Re1 M = Re) with HP(O)R 2 (R = C 6 F 5 , Ph, and OEt) and HP(S)Ph 2 , which resulted in the selective formation of η 2 -Ephosphorylalkene complexes Cp(CO) 2 M{η 2 -E-H[R 2 (O)P]CC(H)Ph} (Mn2, Re2 R = C 6 F 5 ; Mn3, Re3 R = Ph; and Mn6, Re6 R = OEt) and Cp(CO) 2 M{η 2 -E-H[Ph 2 (S)P]C C(H)Ph} (Mn5, Re5). The DFT/B3LYP(6-31G*) analysis showed the model reactions of Mn1 with HP(O)Me 2 and HP(O) (OMe) 2 to procee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Rhodium catalysts were also used to hydrophosphinylate alkynes under microwave irradiation and yielded mono- or double addition products, depending on the loading of the phosphine oxide . Manganese and rhenium catalysts have also been used to effect the single or double hydrophosphinylation of terminal aryl acetylenes, although both required high temperatures …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhodium catalysts were also used to hydrophosphinylate alkynes under microwave irradiation and yielded mono- or double addition products, depending on the loading of the phosphine oxide . Manganese and rhenium catalysts have also been used to effect the single or double hydrophosphinylation of terminal aryl acetylenes, although both required high temperatures …”
Section: Introductionmentioning
confidence: 99%
“…13 Manganese and rhenium catalysts have also been used to effect the single or double hydrophosphinylation of terminal aryl acetylenes, although both required high temperatures. 14 Overall, the hydrophosphination and hydrophosphinylation of acetylenes are both known reactions that have been achieved using a variety of catalysts. In the reported systems, these addition reactions have thus far only been studied independently and have not been examined simultaneously utilizing the same catalytic system.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We performed a computational study with the aid of density functional theory (DFT) methods to investigate the Pd-catalyzed hydrophosphorylation of terminal alkynes with P­(O)–H compounds . We found that the hydrophosphorylation proceeds via switchable mechanisms that are influenced by the acidity of substrates and co-catalysts.…”
Section: Introductionmentioning
confidence: 99%